Addition of omega-3 carboxylic acids to statin therapy in patients with persistent hypertriglyceridemia. (September 2014) - Davidson, Michael H; Phillips, Alyssa K; Kling, Douglas; Maki, Kevin C
<x xml:space="preserve">Abstract</x> The incidence of hypertriglyceridemia has grown alongside that of obesity. Statin therapy has been widely recommended for the treatment of dyslipidemias. Omega-3 (OM3) fatty acid concentrates are commonly prescribed concurrently with statins in patients with persistent hypertriglyceridemia for additional lowering of triglyceride and non-HDL cholesterol. The bioavailability of currently available OM3 ethyl ester drugs is limited by their need for hydrolysis by pancreatic lipases, largely stimulated by dietary fat, prior to intestinal absorption. This review will discuss the chemistry, pharmacokinetics and clinical efficacy of a novel OM3 carboxylic acid drug that provides polyunsaturated docosahexaenoic and eicosapentaenoic acids in the free fatty acid form, which is readily absorbed by the intestine. This drug was approved in May 2014 as an adjunct to diet to reduce triglyceride levels in adults with severe (≥500 mg/dl) hypertriglyceridemia.